The Fairy-Tale Detectives : The Sisters Grimm #1 - Buckley, Michael, 1969-; Ferguson, Peter, 1968- (New York : Amulet Books, 2007)
Orphans Sabrina and Daphne Grimm are sent to live with an eccentric grandmother that they have always believed to be dead.
Keywords: Sisters -- Fiction; Orphans -- Fiction; Grandmothers -- Fiction; Monsters -- Fiction